2022
DOI: 10.1111/add.15889
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive brain stimulation for smoking cessation: a systematic review and meta‐analysis

Abstract: Background and Aims: Non-invasive brain stimulation (NIBS) methods have showed promising results for the treatment of tobacco use disorder, but little is known about the efficacy of NIBS on sustained tobacco abstinence. We aimed to assess its effectiveness for long-term smoking cessation.Methods: Systematic review and meta-analysis of randomized controlled trials (RCT).PubMed, Cochrane library, Embase, PsycINFO and clinical trials registries were systematically searched for relevant studies up to May 2021. Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 71 publications
0
4
0
1
Order By: Relevance
“…Brain stimulation is currently viewed as a promising therapy for smoking cessation [81,82] and studies targeting the insula have demonstrated mixed success in affecting smoking-related variables, such as craving and withdrawal [13,16]. TMS has received clearance by the U.S. Food and Drug Administration for smoking cessation [83], and while several studies have shown encouraging results, including one indicating that high-frequency deep TMS to the insula and prefrontal cortex reduces nicotine dependence [84], others have shown weak or no effects [13,45].…”
Section: Discussionmentioning
confidence: 99%
“…Brain stimulation is currently viewed as a promising therapy for smoking cessation [81,82] and studies targeting the insula have demonstrated mixed success in affecting smoking-related variables, such as craving and withdrawal [13,16]. TMS has received clearance by the U.S. Food and Drug Administration for smoking cessation [83], and while several studies have shown encouraging results, including one indicating that high-frequency deep TMS to the insula and prefrontal cortex reduces nicotine dependence [84], others have shown weak or no effects [13,45].…”
Section: Discussionmentioning
confidence: 99%
“…La plupart des études évaluant la SMTr comme thérapie antitabagique se sont penchées sur les effets générés lorsqu’on cible le cortex préfrontal dorsolatéral à l’aide de bobines en forme de 8. Ces études de moindre envergure ont rapporté des résultats mitigés et non concluants 7 . Depuis 2014, la bobine H4 — une bobine en H qui cible l’insula et le cortex préfrontal de façon bilatérale — a été utilisée dans 2 essais cliniques.…”
Section: Quelles Sont Les Données Probantes Appuyant L’usage De La Sm...unclassified
“…These smaller studies reported mixed, inconclusive results. 7 Since 2014, the H4-coil -an H-coil that targets the insula and prefrontal cortex bilaterally -has been used in 2 clinical trials. As both trials that used the H4-coil had positive results, it is the only coil that has received approval for smoking cessation from Health Canada.…”
Section: What Is the Evidence To Support Use Of Rtms For Smoking Cess...mentioning
confidence: 99%